Analisis Asam Salisilat pada Krim Wajah yang Beredar di Pasar Besar Kota Malang - Lukky Jayadi (JURNAL FARMASI DAN MAKANAN, 2022)
Salicylic acid is a skin remedy that is used to treat various skin problems such as acne. Salicylic acid is safe to use and contains Beta Hydroxy Acid (BHA), which is an ingredient used to reduce wrinkles and acne. Although it has benefits for removing acne, salicylic acid is a dangerous chemical if used in excess of the prescribed limits. To determine the levels of salicylic acid in anti acne creams circulating in Pasar Besar Malang City, qualitatively with color test using FeCl3 and quantitatively using UV-Vis spectrophotometry to analyze levels of salicylic acid in anti-acne cream. Qualitative research using FeCl3 showed that from four samples, one sample was declared negative, while three positive samples contained salicylic acid, while testing using UV-Vis spectrophotometry found all samples containing salicylic acid. The levels of salicylic acid in all samples were within the safe limits set by BPOM with the highest level contained in skin surface products, including substances harmful to the skin, should not be more than 2%.